Murach's python programming - Urban,Michael (Shroff, 2018)
If you want to learn how to program but don't know where to start, this is the right book and the right language for you. From the first page, our unique self-paced approach will help you build competence and confidence in your programming skills. And Python is the best language ever for learning how to program because of its simplicity and breadth...two features that are hard to find in a single language.